A prospective study to assess in vivo optical coherence tomography imaging for early detection of chemotherapy‐induced oral mucositis1. Issue 1 (15th January 2013) - Calantog, Alden; Hallajian, Lucy; Nabelsi, Tasneem; Mansour, Stephanie; Le, Anh; Epstein, Joel; Wilder‐Smith, Petra
Abstract Background and Objective Oral mucositis (OM) is a common and severe complication of many cancer therapies. Currently, prediction and early detection are not possible and objective monitoring remains problematic. Goal of this prospective study is to assess non‐invasive imaging using optical coherence tomography (OCT) for early detection and evaluation of chemotherapy‐induced OM in 48 patients, 12 of whom developed clinical mucositis. Study Design/Materials and Methods In 48 patients receiving neoadjuvant chemotherapy for primary breast cancer, oral mucosal health was assessed clinically, and imaged using non‐invasive OCT. Images were evaluated for mucositis using an imaging‐based scoring system ranging from 0 to 6. Conventional clinical assessment using the OM assessment scale (OMAS) was used as the gold standard. Patients were evaluated on Days 0–11 after commencement of chemotherapy. OCT images were visually scored by three blinded investigators. Results The following events were identified from OCT images (1) change in epithelial thickness and subepithelial tissue integrity (beginning on Day 2), (2) loss of surface keratinized layer continuity (beginning on Day 4), (3) loss of epithelial integrity (beginning on Day 4). Imaging data gave higher scores compared to clinical scores early in treatment, suggesting that the imaging‐based diagnostic scoring was more sensitive to early mucositic change than the clinical scoring system. Once mucositis was established, imaging and clinical scores converged. Conclusion Using OCT imaging and a novel scoring system, earlier, more sensitive detection of mucositis was possible than using OMAS. Specific imaging‐based changes were a consistent predictor of clinical mucositis. Lasers Surg. Med. 45: 22–27, 2013. © 2013 Wiley Periodicals, Inc.